Study more tomorrow - Pugatch, Todd,Schroeder, Elizabeth,Wilson, Nicholas (Global Labor Organization (GLO), 2022)
We design a commitment contract for college students,
10419/260491
Keywords: Graue Literatur; economics of education; higher education; commitment contracts; randomized control trials